Gating of a pH-sensitive K(2P) potassium channel by an electrostatic effect of basic sensor residues on the selectivity filter. - Leandro Zúñiga (PLoS ONE, 2011)
K(+) channels share common selectivity characteristics but exhibit a wide diversity in how they are gated open. Leak K(2P) K(+) channels TASK-2, TALK-1 and TALK-2 are gated open by extracellular alkalinization. The mechanism for this alkalinization-dependent gating has been proposed to be the neutralization of the side chain of a single arginine (lysine in TALK-2) residue near the pore of TASK-2, which occurs with the unusual pK(a) of 8.0. We now corroborate this hypothesis by transplanting the TASK-2 extracellular pH (pH(o)) sensor in the background of a pH(o)-insensitive TASK-3 channel, which leads to the restitution of pH(o)-gating. Using a concatenated channel approach, we also demonstrate that for TASK-2 to open, pH(o) sensors must be neutralized in each of the two subunits forming these dimeric channels with no apparent cross-talk between the sensors. These results are consistent with adaptive biasing force analysis of K(+) permeation using a model selectivity filter in wild-type and mutated channels. The underlying free-energy profiles confirm that either a doubly or a singly charged pH(o) sensor is sufficient to abolish ion flow. Atomic detail of the associated mechanism reveals that, rather than a collapse of the pore, as proposed for other K(2P) channels gated at the selectivity filter, an increased height of the energetic barriers for ion translocation accounts for channel blockade at acid pH(o). Our data, therefore, strongly suggest that a cycle of protonation/deprotonation of pH(o)-sensing arginine 224 side chain gates the TASK-2 channel by electrostatically tuning the conformational stability of its selectivity filter.